2018
DOI: 10.1016/j.ajog.2018.05.020
|View full text |Cite
|
Sign up to set email alerts
|

To the point: gender differences in the obstetrics and gynecology clerkship

Abstract: Gender differences in performance on the obstetrics and gynecology clerkship have been reported, with female students outperforming male students. Male students report that their gender negatively affects their experience during the clerkship. Additionally, there are fewer male students applying for obstetric/gynecology residency. This "To The Point" article by the Association of Professors of Gynecology and Obstetrics Undergraduate Medical Education Committee will describe the gender differences that have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 42 publications
(47 reference statements)
0
23
0
Order By: Relevance
“…In particular, the ObGyn clerkship has been targeted as critical in terms of recruiting future residents to the speciality. 1,[4][5][6] Research has shown that male students experience their gender as a barrier in ObGyn training and that this may increase the number of male students who choose not to pursue careers within the field. 6,7 The feeling of having a disadvantage because of one's male gender may be due to being denied consent to participate in clinical care to a greater degree than female students.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the ObGyn clerkship has been targeted as critical in terms of recruiting future residents to the speciality. 1,[4][5][6] Research has shown that male students experience their gender as a barrier in ObGyn training and that this may increase the number of male students who choose not to pursue careers within the field. 6,7 The feeling of having a disadvantage because of one's male gender may be due to being denied consent to participate in clinical care to a greater degree than female students.…”
Section: Introductionmentioning
confidence: 99%
“…The number of female O&Gs in Australia and New Zealand has been steadily increasing and currently women make up half of all Fellows of RANZCOG 11,12 . With rapidly increasing numbers of women in our specialty, 13,14 the issue of WRMI will be of greater concern and more research is needed on ways to minimise its impact on the workforce.…”
Section: Discussionmentioning
confidence: 99%
“…Although “specificity of women's treatment,” which can only be experienced in Ob/Gyn, was generally associated with positive impression change among the non‐Ob/Gyn applicants, delicate aspects of the training may have fostered negative impression change. In Ob/Gyn training, male interns are often subjected to gender bias from their patients and often feel that their gender negatively affects their practice experience 4, 5 . The training system should be prepared to assist male interns.…”
Section: Discussionmentioning
confidence: 99%